2022
DOI: 10.1186/s41073-022-00125-x
|View full text |Cite
|
Sign up to set email alerts
|

Reducing the Inadvertent Spread of Retracted Science: recommendations from the RISRS report

Abstract: Background Retraction is a mechanism for alerting readers to unreliable material and other problems in the published scientific and scholarly record. Retracted publications generally remain visible and searchable, but the intention of retraction is to mark them as “removed” from the citable record of scholarship. However, in practice, some retracted articles continue to be treated by researchers and the public as valid content as they are often unaware of the retraction. Research over the past… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 78 publications
0
11
0
2
Order By: Relevance
“…Our deviation from COPE guidelines was for instances where we were unable to determine the reasons for retraction, which we captured as “unknown” (if we could not retrieve the text), or “undefined” (if unstated on either the link to the text or the text itself). Furthermore, since we were unable to retrieve pre-prints for studies which were published, we could not document whether or not they had been withdrawn with watermarks, which has been recommended in publication ethics to reduce citation of retracted research [ 8 , [19] , [20] , [21] ].…”
Section: Methodsmentioning
confidence: 99%
“…Our deviation from COPE guidelines was for instances where we were unable to determine the reasons for retraction, which we captured as “unknown” (if we could not retrieve the text), or “undefined” (if unstated on either the link to the text or the text itself). Furthermore, since we were unable to retrieve pre-prints for studies which were published, we could not document whether or not they had been withdrawn with watermarks, which has been recommended in publication ethics to reduce citation of retracted research [ 8 , [19] , [20] , [21] ].…”
Section: Methodsmentioning
confidence: 99%
“…Sometimes, authors have downloaded a paper before it was retracted. Often, bibliographies and other databases where authors can check their references lack information about retractions (Marcus et al, 2022; Schneider et al, 2022). Retracted papers are also often available in full text, without any indication of the retraction, in other places than the publisher's website.…”
Section: Make It Easier For Authors!mentioning
confidence: 99%
“…They concluded that further analysis of systematic reviews citing retracted publications is needed to determine the impact of flawed data. Schneider et al (2022) report recommendations from an initiative to reduce inadvertent citation of retracted publications, including developing an approach to ensure the public availability of consistent, standardized, interoperable, and timely information about retractions. Another threat to systematic review quality is publication bias, when a study does not result in a publication that can be included as part of the review.…”
Section: Assessment Of Review Qualitymentioning
confidence: 99%